(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
In this article, I investigate the role of color in visual compositions of contemporary theater, emphasizing its importance in creating meanings, atmospheres and emotions in the scenic space through images. I propose a reflection on the conception of color not only as a physical phenomenon perceived by the human eye, but also as an aesthetic element essential. In addition to exploring the scientific aspects, I approach color under the perspective of the spectator’s experience, based on reflections developed by artists such as Hélio Oiticica and Kandinsky.